2014
DOI: 10.1242/dev.105130
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3L promotes quiescence in postnatal spermatogonial progenitor cells

Abstract: The ability of adult stem cells to reside in a quiescent state is crucial for preventing premature exhaustion of the stem cell pool. However, the intrinsic epigenetic factors that regulate spermatogonial stem cell quiescence are largely unknown. Here, we investigate in mice how DNA methyltransferase 3-like (DNMT3L), an epigenetic regulator important for interpreting chromatin context and facilitating de novo DNA methylation, sustains the long-term male germ cell pool. We demonstrated that stem cell-enriched TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 87 publications
2
44
2
Order By: Relevance
“…In a previous study, DNMT3L was expressed only in germ cells, and the expression pattern was observed in males and females (77). However, in males, DNMT3L was initially detected at 12.5 days after fertilization of the egg, and the levels peaked at 15.5 days and remained upregulated until birth (77)(78)(79). However, the expression of DNMT3L was significantly 79 following birth and was found to be low in mature germ cells (36)(37)(38), suggesting an association between DNMT3L and DNA methylation.…”
Section: Dna Methylation and Spermatogenesismentioning
confidence: 84%
See 1 more Smart Citation
“…In a previous study, DNMT3L was expressed only in germ cells, and the expression pattern was observed in males and females (77). However, in males, DNMT3L was initially detected at 12.5 days after fertilization of the egg, and the levels peaked at 15.5 days and remained upregulated until birth (77)(78)(79). However, the expression of DNMT3L was significantly 79 following birth and was found to be low in mature germ cells (36)(37)(38), suggesting an association between DNMT3L and DNA methylation.…”
Section: Dna Methylation and Spermatogenesismentioning
confidence: 84%
“…In certain individuals with deletion mutations in DNMT genes, a proportion of the paternal differentially methylated regions (DMRs) were normal, which suggested that DNMTs have some functional duplication (77)(78)(79). Notably, oocytes lacking DNMT3L were able to undergo normal meiosis and exhibited methylation of repeat sequences; however, a significant lack of methylation-mediated imprinting existed only in the female imprinting positions (48)(49)(50)(51)(52).…”
Section: Dna Methylation and Spermatogenesismentioning
confidence: 99%
“…DNA methyltransferase 3-like (DNMT3L) is involved in SSC quiescence. DNMT3L positively regulates the stability of promyelocytic leukemia zinc finger (PLZF) in THY1 C SSCs through down-regulating CDK2 expression, which may degrade PLZF through the ubiquitin pathway (Liao et al 2014). The distal CpG island of Cdk2 promoter has been shown to be hypomethylated in Dnmt3l-knockout SSCs compared to the wide-type cells (Liao et al 2014).…”
Section: Dna Methylation and Ssc Division And Differentiationmentioning
confidence: 99%
“…DNMT3L positively regulates the stability of promyelocytic leukemia zinc finger (PLZF) in THY1 C SSCs through down-regulating CDK2 expression, which may degrade PLZF through the ubiquitin pathway (Liao et al 2014). The distal CpG island of Cdk2 promoter has been shown to be hypomethylated in Dnmt3l-knockout SSCs compared to the wide-type cells (Liao et al 2014). On the other hand, it has been reported that the expression of DNMT3a2 and DNMT3b is undetectable in PLZF-positive and KIT-negative SSCs (Shirakawa et al 2013 members of DNMT3 subfamily in regulating mitotic self-renewal of mouse SSCs.…”
Section: Dna Methylation and Ssc Division And Differentiationmentioning
confidence: 99%
“…Thus, the competition between PLZF and SALL4 is an important topic of investigation. It has been recently shown by Liao et al (2014) that reduced levels of PLZF in Dnmt3l-knockout Thy1 C cells results in the releases of the PLZF antagonist SALL4, which is associated with maintaining the delicate balance of cycling and quiescent SSCs/progenitor cells. Further study is required to investigate whether SALL4 C / PLZF K A single and A paired spermatogonia are destined to differentiate.…”
Section: Introductionmentioning
confidence: 99%